2017
DOI: 10.1038/srep46112
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale SNP discovery and construction of a high-density genetic map of Colossoma macropomum through genotyping-by-sequencing

Abstract: Colossoma macropomum, or tambaqui, is the largest native Characiform species found in the Amazon and Orinoco river basins, yet few resources for genetic studies and the genetic improvement of tambaqui exist. In this study, we identified a large number of single-nucleotide polymorphisms (SNPs) for tambaqui and constructed a high-resolution genetic linkage map from a full-sib family of 124 individuals and their parents using the genotyping by sequencing method. In all, 68,584 SNPs were initially identified using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 52 publications
1
37
0
Order By: Relevance
“…The reduced cost of the new genotyping by sequencing (GBS) techniques has facilitated the development of highly dense genetic maps in aquaculture fish species, 3 , 17–19 including turbot 21 . Here, we combined for the first time a high number of markers and families for a deep mapping analysis aimed at integrating genetic and physical map resources in turbot to understand its genome organisation and variation, a study not performed to date in fish 23 , 58 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduced cost of the new genotyping by sequencing (GBS) techniques has facilitated the development of highly dense genetic maps in aquaculture fish species, 3 , 17–19 including turbot 21 . Here, we combined for the first time a high number of markers and families for a deep mapping analysis aimed at integrating genetic and physical map resources in turbot to understand its genome organisation and variation, a study not performed to date in fish 23 , 58 .…”
Section: Discussionmentioning
confidence: 99%
“…High-density (HD) genetic maps provide information on genome organisation by establishing the cartography of thousands of markers, which can aid to disentangle the genetic architecture of productive or evolutionary traits. Moreover, these maps represent an essential tool for comparative genomics and can facilitate whole genome assembly 2 , 3 . The advent of next generation sequencing (NGS) has dramatically reduced the cost and time required for genomic analysis, 4 , 5 thus contributing to a fast increase of genomic resources.…”
Section: Introductionmentioning
confidence: 99%
“…Studies estimating CO rates from linkage disequilibrium in population samples, presenting information from a single chromosome only, or performed with low marker resolution (fewer than ~20 markers per chromosome on average) were ignored. In a single case (Nunes et al., ), we considered a marker‐dense data set presenting genetic map position against marker order (instead of Mb position in a physical assembly). Visually comparing patterns of cM vs. Mb to cM vs. marker order in another organism in which both data types were available (Dohm et al., , ) confirmed that the latter data type also reliably captures broad‐scale CO patterns (see also Nachman & Churchill, ).…”
Section: Methodsmentioning
confidence: 99%
“…Next, we defined the length of each chromosome as the Mb position of the terminal marker interval mid‐point, calculated mean CO periphery‐bias and chromosome length across the chromosomes within each species and assessed if chromosome length predicted the CO distribution when using species as data points. This was carried out using Spearman's rank correlation (hereafter simply “correlation” because we always applied the Spearman method to quantify the strength of association between variables) and included all species except the single one lacking physical chromosome positions (Nunes et al, ). The correlation between CO periphery‐bias and chromosome length was further explored within species (i.e., using chromosomes as data points).…”
Section: Methodsmentioning
confidence: 99%
“…Hybrid fish originating from serrasalmid species such as the pacu (P. mesopotamicus), tambaqui (C. macropomum) and pirapitinga (P. brachypomus), or from pimelodid species such as the pintado (P. corruscans) and cachara (Pseudoplatystoma reticulatum), are considered commercially valuable and have high growth rates and have other characteristics that are useful to the commercial sector such as resistance and better reproductive performance [199]. The interest in hybrid production may be due to the lack of knowledge about the pure species, mainly in genetic breeding approaches [200].…”
Section: Identification Of Neotropical Hybrid Fishmentioning
confidence: 99%